INNOVATIVE TECHNOLOGIES IN TEACHING ENGLISH ИННОВАЦИОННЫЕ ТЕХНОЛОГИИ В ОБУЧЕНИИ АНГЛИЙСКОМУ ЯЗЫКУ - Elmurodova Guljakhon (Journal of new century innovations, 2022)
the role and the effective usage of innovative technologies in teaching English are considered in this article. The Internet links, which are effectively used during the lessons, are also shown here